Avaliação das técnicas de VDRL e teste rápido como triagem para sífilis em gestantes de um município da região norte do Espírito Santo, Brasil - Maciel, Janaina dos Santos (2019)
Syphilis is a systemic disease caused by Treponema pallidum. Known since the fifteenth century, it is an infectious disease sexually transmitted, of chronic evolution, subject to crises of exacerbation and periods of latency. Its diagnosis can be made through treponemic and non-treponemic tests. In order to verify the concordance of the rapid test for syphilis in pregnant women, when compared to VDRL and the need for confirmatory tests, in both pregnant and newborn infants born to pregnant women infected with T. pallidum, a study was performed in a hospital of a medium-sized municipality in northern Espírito Santo. For the analysis in the pregnant women the rapid tests, the VDRL test were applied, and in the case of positivity for one or both tests, the confirmatory examination was applied TPHA. The results indicated that 93 (33.7%) of the 276 samples were positive for one or both methods, but only 89 (32.2%) remained positive when the confirmatory test was performed, and that 35 (39.3%) pregnant women, with the diagnosis for syphilis confirmed through the TPHA, were positive only for rapid test. The VDRL and TPHA tests were applied in the newborns and the study detected a 61.0% (25) positivity rate in infants born to syphilis mothers using the VDRL nontreponemal test, while using the treponemic test (TPHA) was detected 97.6% (40). A demographic characterization of the pregnant women was carried out using a questionnaire and a prevalence profile of syphilic women of fertile age of 47.4%, married and with up to 11 years of schooling of 68.4% and 94.8%, respectively, corroborating the results found in other studies. The results indicated that there is a need for adjustment in the diagnostic procedure for neonates, considering the use of a treponemal test and that the implementation of the rapid test in prenatal care can provide early access to the diagnosis and treatment of syphilis in pregnant women and their sexual partners, reduction of acquired syphilis transmission and reinfection and reduction of congenital syphilis cases.